2016
DOI: 10.5539/jas.v8n8p79
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Nile Tilapia (Oreochromis niloticus) Fed Diets Containing Blood Meal as a Replacement of Fish Meal

Abstract: A 100 days experiment was conducted to determine the effect of feeding blood meal (BM) as a replacement of fish meal (FM), as the main source of animal protein, on growth rate and economic performance of Nile tilapia in fertilized pond. Three isonitrogenous diets (35% crude protein) were formulated using either FM as the main source of animal protein (Diet 1); 50% replacement of FM with blood meal (Diet 2); or 100% replacement of FM with BM (Diet 3). Three hundred Nile tilapia fingerlings (12±3 g) were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Food intake per fish was calculated at each sampling time, using the average body weight (ABW), the total no of fish ( N ) in a tank and the amount of feed consumed per day (AFd −1 ): Feed intake = ABW × N × AFd −1 (Adene, 2020). The RGR (Kirimi et al, 2016; Lugert et al, 2014) and SGR, FCR and PER (Li et al, 2009; Ogunji et al, 2020) were calculated as follows: RGR (final fish weight − initial fish weight/time, multiplied by 100 and expressed in %), SGR = (ln W f − ln W i / T ) × 100 (where T = no. of days the experiment lasted); FCR = feed intake (g)/fish weight gain (g); PER = weight gain/protein intake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food intake per fish was calculated at each sampling time, using the average body weight (ABW), the total no of fish ( N ) in a tank and the amount of feed consumed per day (AFd −1 ): Feed intake = ABW × N × AFd −1 (Adene, 2020). The RGR (Kirimi et al, 2016; Lugert et al, 2014) and SGR, FCR and PER (Li et al, 2009; Ogunji et al, 2020) were calculated as follows: RGR (final fish weight − initial fish weight/time, multiplied by 100 and expressed in %), SGR = (ln W f − ln W i / T ) × 100 (where T = no. of days the experiment lasted); FCR = feed intake (g)/fish weight gain (g); PER = weight gain/protein intake.…”
Section: Methodsmentioning
confidence: 99%
“…Increase in dietary CBM from CBM2 (25%) to CBM4 (33%) resulted to a significant decrease in the growth of fish, thus could be attributed to high dietary inclusion of CBM which probably led to underutilization of diets. Kirimi et al (2016) reported a decreased growth performance with increased levels of blood meal in their experimental diets. Glencross et al (2007) remarked that the growth and feed utilization of fish fed plant and animal alternative protein sources are usually affected by palatability, digestibility and amino acid balance of FM feedstuff substitutes.…”
Section: Growth Performance and Feed Utilizationmentioning
confidence: 99%
“…In comparison with other plant‐derived by‐products, blood meal offered more scope for inclusion and was better accepted by rohu under the prevailing experimental conditions. Kirimi et al 133 conducted a study where Nile tilapia ( O . niloticus ) were fed on diets containing 12.5% and 25% blood meal, respectively.…”
Section: Abps Available To Aquaculturementioning
confidence: 99%
“…High levels of essential amino acids in fish meal as in the present study make it more desirable in fish feed. However, the high costs and scarcity in Kenya is the major limitation to its use (Kirimi, Musalia, Magana, & Munguti, 2016b).…”
Section: Amino Acid Profile Of Feed Ingredientsmentioning
confidence: 99%